Low dose aspirin prevents endothelial dysfunction in the aorta and foetal loss in pregnant mice infected with influenza A virus - Coward-Smith, Madison; Liong, Stella; Oseghale, Osezua; Erlich, Jonathan R.; Miles, Mark A.; Liong, Felicia; Brassington, Kurt; Bozinovski, Steven; Vlahos, Ross; Brooks, Robert D.; Brooks, Doug A.; O’Leary, John J.; et al. (Frontiers in Immunology, 2024)
Influenza A virus (IAV) infection in pregnancy resembles a preeclamptic phenotype characterised by vascular dysfunction and fetal growth retardation. Given that low dose aspirin (ASA) is safe in pregnancy and is used to prevent preeclampsia, we investigated whether ASA or NO-conjugated aspirin, NCX4016, resolve vascular inflammation and function to improve offspring outcomes following IAV infection in pregnant mice. Pregnant mice were intranasally infected with a mouse adapted IAV strain (Hkx31; 10 4 plaque forming units) and received daily treatments with either 200µg/kg ASA or NCX4016 via oral gavage. Mice were then culled and the maternal lungs and aortas collected for qPCR analysis, and wire myography was performed on aortic rings to assess endothelial and vascular smooth muscle functionality. Pup and placentas were weighed and pup growth rates and survival assessed. IAV infected mice had an impaired endothelial dependent relaxation response to ACh in the aorta, which was prevented by ASA and NCX4016 treatment. ASA and NCX4016 treatment prevented IAV dissemination and inflammation of the aorta as well as improving the pup placental ratios in utero, survival and growth rates at post-natal day 5. Low dose ASA is safe to use during pregnancy for preeclampsia and this study demonstrates that ASA may prove a promising treatment for averting the significant vascular complications associated with influenza infection during pregnancy.